Time Effect on Aerobic Composting Method for Temperature and pH from Brem Waste - Kindriari Nurma Wahyusi; Ummi Muashomah; Annisa Bella; Nur Aini Fauziyah (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2021)
This research addressed to utilize brem waste to be compost with the addition of M-Bio activator using aerobic composting method. Brem waste was collected from brem industry, UD. Tongkat Mas, located in the Caruban, Madiun, East Java. The main material was brem waste (1 kg) with additional materials of eggshell flour (300 g) and M-Bio activator. Here, we considered every time and the pH was measured every time interval. This brem waste was included in organic waste. This organic waste had a high water content so it can easily decompose. The temperature of compost increased as addition of M-Bio activator. The best properties was shown by the compost III that met with the standards SNI 19-7030-2004.